Metasurface‐Assisted Wireless Communication with Physical Level Information Encryption. Issue 34 (17th October 2022) - Zheng, Yilin; Chen, Ke; Xu, Zhiyuan; Zhang, Na; Wang, Jian; Zhao, Junming; Feng, Yijun
Abstract: Since the discovery of wireless telegraphy in 1897, wireless communication via electromagnetic (EM) signals has become a standard solution to address increasing demand for information transfer in modern society. With the rapid growth of EM wave manipulation technique, programmable metasurface (PM) has emerged as a new type of wireless transmitter by directly modulating digital information without complex microwave components, thus providing an alternative to simplify the conventional wireless communication system. However, the challenges of improving information security and spectrum utilization still exist. Here, a dual‐band metasurface‐assisted wireless communication scheme is introduced to provide additional physical channels for the enhancement of information security. The information is divided into several parts and transmitted through different physical channels to accomplish information encryption, greatly reducing the possibility of eavesdropping. As the proof of concept, a dual‐channel and high‐security wireless communication system based on a 1‐bit PM is established to simultaneously transmit two different parts of a picture to two receivers. Experiments show that the transmitted picture can be successfully retrieved only if the received signals of different receivers are synthetized as predefined. The proposed scheme provides a new route of employing PM in information encryption and spectrum utilization of wireless communication. Abstract : A metasurface‐assisted wireless communication prototype system with additional physical channels to enhance the information security is proposed here. The information is divided into several parts and transmitted simultaneously through different frequency‐channels to avoid eavesdropping. The system demo proves that a colour picture can be successfully encrypted and retrieved with high reliability.